2000
DOI: 10.1677/jme.0.0240273
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-2 synthesis is stimulated by the type-1 tumour necrosis factor receptor and cAMP: comparison with endothelin-converting enzyme-1 expression

Abstract: The synthesis of the vasoconstrictor peptide endothelin-2 (ET-2) is dependent on hydrolysis of the biologically inactive intermediate big ET-2 by an endothelin-converting enzyme (ECE). Here, mechanisms inducing ET-2 synthesis have been investigated using the human renal adenocarcinoma cell line (ACHN). Synthesis of ET-2 by ACHN cells was inhibited by phosphoramidon (IC(50( congruent with11 microM). To determine whether ET-2 synthesis occurs in parallel with the metallopeptidase ECE-1, a putative processing pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…4B). To determine where endothelin-converting enzyme 1 (ECE-1), an enzyme implicated in the processing of big EDN2 to mature EDN2 [37], is expressed in retina, we used immunofluorescence staining. We found that ECE-1 was expressed in Müller cell bodies and radial fibres (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B). To determine where endothelin-converting enzyme 1 (ECE-1), an enzyme implicated in the processing of big EDN2 to mature EDN2 [37], is expressed in retina, we used immunofluorescence staining. We found that ECE-1 was expressed in Müller cell bodies and radial fibres (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(1991) demonstrated an inhibitory effect of epidermal growth factor in the production of ET‐2 but not ET‐1 in renal adenocarcinoma cells. Lambert et al . (1998; 2000) explored compounds regulating expression of ET‐2 mRNA and secretion of the peptide in human renal adenocarcinoma cell lines.…”
Section: Regulation Of Et Genesmentioning
confidence: 99%